THE EFFECT OF BUILDING ORIENTATION ON FACADES IN THE LINE OF BALUWARTI BUILDING KRATON YOGYAKARTA - Adianti, Istiana; Vidya A, Nurina (Border: Jurnal Arsitektur, 2019)
Various methods are used by humans to respond to an uncomfortable climate. Indonesia has a wet tropical climate where the air temperature and humidity are quite high. Tembok Baluwarti of Yogyakarta Palace functions to encircle the area of the Sultan's residence and Abdi Dalem's settlement as well as the soldier's inspection line. Significant changes in form and function occur when HB VI allows outside Beteng residents to live temporarily in an open place inside and around Beteng. The east and west side settlements are considered to have no thermal comfort compared to the other side. The building and opening orientation factors influence the architectural design to increase thermal comfort in wet tropical climates. The solution to solving the thermal comfort problems carried out by each occupant in most residential and commercial buildings is that they add a trellis or extension of the roof width, then use banners/banners/bamboo to help block the heat of the sun, and the last strategy is to add vegetation in front of his house.